Propuesta de implementación de un sistema de aseguramiento de calidad de bienestar animal, basada en la norma ISO 26000 y en un HACCP en el albergue criar en el periodo marzo – junio 2020 - Muñoz Romero, Lesly Dayana (2020)
The ISO 26000 standard is focused on animal welfare based on corporate social responsibility management systems, that is, associations, companies, entities can and should manage programs for the benefit of animal welfare. The interest of this agreement is that within the ethical conduct of companies is compliance with standards that ensure animal welfare, applying what is indicated by the World Organization for Animal Health (OIE), WHO and regarding the Sanitary Code of Land animals. The HACCP system allows identifying hazards from the collection and evaluation of information to apply corrective measures to control critical points. The objective of this study was to create a proposal for the implementation of an animal welfare quality assurance system, based on the ISO 26000 standard and a HACCP in the CRIAR shelter, which was carried out through the use of surveys, interviews to the technical and cleaning staff of the shelter and through an on-site visit, in order to know the current situation of the shelter, identify the critical points, for the creation of a proposal for improvements in animal welfare, by analyzing the survey conducted through the Forms platform. As a result, critical points were found such as: cleaning, deep disinfection, management of the quarantine area, capacity to house refugee animals and management of sanitary plans. At the end of the study, it was concluded that the provisions of the shelter guide are not fully complied with, nor what the shelter legislation indicates, therefore, there is an average degree of animal welfare within the shelter, which could be improved with the application of the suggested improvement proposal.